Compost tea spraying increases yield performance of pepper (Capsicum annuum L.) grown in greenhouse under organic farming system - Zaccardelli, Massimo; Pane, Catello; Villecco, Domenica; Palese, Assunta Maria; Celano, Giuseppe (Italian Journal of Agronomy, 2018)
Compost tea (CT) is an organic liquid product derived from quality compost carrying useful microorganism and molecules capable to protect and stimulate growth of the plants. It is gaining a lot of interest for improving productivity of conventional and/or organic vegetable crops. In this research, the effects of an aerated water-extracted CT obtained from vegetable composts, applied as foliar spray on pepper plants, was evaluated for two years. In the first year, total production increased by 21.9% whereas, in the second year, it increased by 16.3%. The increment of the yields was related to an increase of the number of fruits per plant, whereas the weight of the single fruit was not affected by treatment. In both years, physiological and nutritional status of pepper plants were increased, as resulted by leaf-SPAD assessed during crop cycle. Findings indicate the effectiveness of CT application in improving significantly yield performances of vegetable crops under greenhouse organic farming system.